Rapporti tra tettonica e clima durante l'esumazione nelle Alpi Centrali. Evidenze dalla termocronologia e dall'analisi strutturale lungo il traforo ferroviario del Sempione - Pignalosa, Antonio <1982> (Alma Mater Studiorum - Università di Bologna, 2009)
(U-Th)/He and fission-track analyses of apatite along deep-seated tunnels crossing high-relief mountain ranges offer the opportunity to investigate climate and tectonic forcing on the topographic evolution. In this study, the thermochronologic analysis of a large set of samples collected in the Simplon railway tunnel (western-central Alps; Italy and Switzerland) and along its surface trace, coupled with kinematic and structural analysis of major fault zones intersecting the tunnel, constrains the phenomena controlling the topographic and structural evolution, during the latest stage of exhumation of the Simplon Massif, and the timing in which they operated. The study area is located at the western margin of the Lepontine metamorphic dome where a complex nappe-stack pertaining to the Penninic and Ultrahelvetic domains experienced a fast exhumation from the latest Oligocene onward. The exhumation was mainly accommodated by a west-dipping low-angle detachment (the Simplon Fault Zone) which is located just 8 km to the west of the tunnel. However, along the section itself several faults related to two principal phases both with important dip-slip kinematics have been detected. Cooling rates derived from our thermocronological data vary from about 10 °C/Ma at about 10 Ma to about 35 °C/Ma in the last 5 Ma. Such increase in the cooling rate corresponds to the most important climatic change recorded in the northern hemisphere in the last 10 Ma, i.e. the shift to wetter conditions at the end of the Messinian salinity crisis and the inception of glacial cycles in the northern hemisphere. In addition, (U-Th)/He and fission-track age patterns lack of important correlation with the topography suggesting that the present-day relief morphology is the result of recent erosional dynamics. More in details, the (U-Th)/He tunnel ages show an impressive uniformity at 2 Ma, whereas cooling rates calculated at 1 Ma increase towards the two major valleys. This indicates a focusing of erosive processes in the valleys which led to the shaping of present-day topography. Structural analysis documents the presence of two phases of brittle deformation postdating the metamorphic phases in the area. The first one is directly related to the last phase of activity along the Simplon Fault Zone and is characterized by extension towards SO and vertical shortening. The young one is characterized by extension towards NO and horizontal shortening in a along the NE-SO direction. Structures related to the first phase of brittle deformation generate important variations in the older ages' dataset, until 3 Ma, suggesting that tectonics controlled rocks exhumation up to that age. Structures related to the second phase generate some variations also in the younger age dataset, highlighting the activity of faults bordering the massif and suggesting a continuous activity also after 2 Ma. However, most of (U-Th)/He tunnel ages, varying slightly around 2 Ma, document that the Simplon area has experienced primarily erosional exhumation in this time span. In conclusion, all our data suggest that in the central Italian Alps the climatic signal gradually overrode the tectonic effects after about 5 Ma, as a consequence of the climatic instability started at end of Messinian salinity crisis and improved by the onset of glaciations in the northern hemisphere.